Preliminary investigation on the tribocorrosion behaviour of nanotubular structured Ti6Al4V surfaces - Rodrigues, N. R.; Alves, A. C.; Toptan, F.; Rocha, L. A. [UNESP] (Elsevier, 2018)
In order to improve its tribocorrosion resistance, nanotubular structures were produced on Ti6Al4V surfaces by anodic treatment in a mixture of 1 M H2SO4 and 0.08 M HF electrolyte. Tribocorrosion tests were performed in a phosphate-buffered saline solution (PBS) against an alumina ball under 50 mN. Results showed that nanostructured surfaces exhibited significantly lower tendency to corrosion due to the protecting effect given by the well-adherent TiO2 nanotubular layer.
Keywords: Nanotubular structures; Ti6Al4V; Tribocorrosion